The Impact of Phasing-out Textile Quota on the Egyptian Textile and Clothing Sector (Case studies from Alexandria) - Farag, Hanan Abouel; Moustafa, El-Sayeda; Mandour, Ahmed (Richtmann Publishing, 2012)
Quantitative restrictions on â€œTextile and Clothingâ€ (T&C) trade were completely removed in January 2005.Consequently, Egyptian T&C exporters have lost the quasi-guaranteed market access to the â€œEuropean Unionâ€ (EU) and â€œUnitedStatesâ€ (US) markets and they became subject to fierce competition in global market. This research aims to empiricallyinvestigate the effect of quota abolishment on the Egyptian T&C sector during the period 1995-2008. Quota phase-out had anegative effect on exports especially to the EU market. However, liberalizing T&C trade was not the only factor causing thedeclining trend of exports, as several domestic and international challenges facing the sector led to reduced competitiveness.Those results were proved by a number of case studies using some of the T&C companies in Alexandria as a sample. Theresults of this research provide guidelines for a development strategy to flourish the sector.